2011
DOI: 10.1002/dmrr.1192
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulopathy in spontaneously obese rhesus monkeys with type 2 diabetes: a stereological study

Abstract: Background Animal models provide insights into the diabetic nephropathy pathogenesis, however, available rodent models do not mirror the heterogeneity of lesions in type 2 diabetic (T2DM) patients, and do not progress to end stage renal disease. Previous studies showed that spontaneously obese T2DM rhesus monkeys develop many of the features of human diabetic glomerulopathy, and may progress to ESRD. Here, in order to further characterize diabetic glomerulopathy in this model, we used electron microscopic ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Using this criteria, none of the normal monkeys had positive Ualbumin, only 1 pre-DM>42 mg; 2 DM with micro-albuminuria and 7 DM with diabetic nephropathy, a distribution highly concentrated in the DM group (45%). This observation is consistent with the report by Najafian et al in spontaneously developed obese, dysmetabolic and diabetic rhesus monkeys [22].…”
Section: Characterization Of Diabetic Nephropathy Phenotypes In Nhpssupporting
confidence: 94%
See 1 more Smart Citation
“…Using this criteria, none of the normal monkeys had positive Ualbumin, only 1 pre-DM>42 mg; 2 DM with micro-albuminuria and 7 DM with diabetic nephropathy, a distribution highly concentrated in the DM group (45%). This observation is consistent with the report by Najafian et al in spontaneously developed obese, dysmetabolic and diabetic rhesus monkeys [22].…”
Section: Characterization Of Diabetic Nephropathy Phenotypes In Nhpssupporting
confidence: 94%
“…With the average body weight just ~1/10 in the cynomolgus monkeys (5-15 kg) compared to human (~75 kg), proportionally, it is reasonable to set Ualbumin at 8-20 mgfor micro-albuminuria and >20 mg for diabetic nephropathy. Although somewhat arbitrary, this criterion, however, fits to the characterization of the monkey colonies in the present and other studies [22]. Using this criteria, none of the normal monkeys had positive Ualbumin, only 1 pre-DM>42 mg; 2 DM with micro-albuminuria and 7 DM with diabetic nephropathy, a distribution highly concentrated in the DM group (45%).…”
Section: Characterization Of Diabetic Nephropathy Phenotypes In Nhpssupporting
confidence: 70%
“…The pharmacological efficacy of treatment in preclinical evaluations performed on monkeys has more relevance for human health than any other species of experimental animals. Monkeys also spontaneously develop T2DM [Najafian et al, 2011]. Therefore, the macaque is an ideal disease model for human T2DM.…”
Section: Selection and Induction Of The Diabetic Animal Modelmentioning
confidence: 99%
“…Some reports also showed no difference with the insulin and C-peptide between spontaneously diabetic and non-diabetic monkeys, 16,27 but some reports are contradictory. 15,23,[28][29][30] The primary reason is likely that the insulin maintains normal at early stage of T2DM, whereas it increases to compensate the insulin resistance later and ultimately decreases or does not express because of β-cells dysfunctions. 29 The concentrations of fasting insulin also depend on age.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, spontaneous NHPs model, in a way, is a more valuable resource for understanding the mechanism and exploring the intervention, because it imitates a natural processes of diabetic or hyperglycaemic in a large proportion of patients and may stabilize the phenotypes once in morbidity. It has been found that spontaneous hyperglycaemic macaques developed nephropathy, 15 retinal denaturation, 16 cardiomyopathy, 17 cardiac dysfunction, 18 α‐synuclein deposition 9 and age‐dependent amyloid‐β (Aβ) pathology, 19–21 which partly is consistent with diabetic or chronic hyperglycaemic patients who may suffer from diabetic kidney disease, diabetic retinopathy, cardiovascular disease, Parkinson's disease (PD) and Alzheimer's disease (AD).…”
Section: Introductionmentioning
confidence: 99%